PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016 - Tuti Kistiyani, 14.05.51.0145; Irsad, Moch. (Students' Journal of Economic and Management, 2018)
This study examines the effect of capital structure, dividend policy, profitability and firm size on company value. This research was conducted at manufacturing companies listed on the BEI periode 2014-2016. The sampling method used purposive sampling with some predetermined criteria, the sample is 100 manufacturing companies and relationship between variable explained by using multiple regression analysis. The result of research indicate that capital structure have a no significant negative, dividend policy have a significant positive, profitability have a no significant positive, and firm size have a significant positive effect to company value. R Square value of 0,156 can describe effect independent variable on company value. Keywords: Capital structure, Dividend policy, Profitability, Firm size and Company Value